CAVERNOUS HEMANGIOMA OF THE TONSIL - DR.NISHA ALICE JOSEPH; DR.NISHA ALICE JOSEPH; DR. G.C.VIJAYA SAI (International Journal of Pharma and Bio Sciences, 2015)
Hemangiomas are hamartomas rather than true neoplasms as they are generally composed of vascular spaces arising from endothelial cells and not by incorporation of nearby vascular channels. In most cases, the diagnosis of hemangioma is based on clinical evaluation. The occurance of hemangioma intonsillar tissue is rare. We report a case of a 10 year-old boy who presented with a mass in the throat noticed 6 months back with occasional bleeding from oral cavity while chewing. The clinical evaluation showed that a pedunculated mass arising from the right tonsillar area.CT Neck confirmed a polypoidal lesion with well enhanced and unenhanced areas. Excision and biopsy of the mass were done under GA and the histopathologic examination reported it as a cavernous hemangioma.